Anaemia in Pregnancy and Its Contributing Factors among Women in a Rural Area of Chattogram District, Bangladesh - Jahan, Sadia Tasnuva; Sultana, Sadia (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Maternal anaemia alludes to a condition characterized by a reduction in the number of red blood cells or the amount of haemoglobin during pregnancy; haemoglobin is the protein responsible for transporting oxygen throughout the body. In contemporary times it is an ongoing public health concern. Objectives: To explore the association of maternal anaemia with its contributing factors among women living in a rural area of Chattogram district in Bangladesh. Methods: This cross-sectional, descriptive study was conducted among 146 pregnant women having some sorts of clinical anaemia, who came at Sitakunda Upazila Health Complex, Chattogram, Bangladesh, between July and December of 2023. A pre-tested, semi-structured questionnaire as well as patient data sheet were used for data collection through face-to-face interviews. Results: Among 146 participants, 74(50.7%) belonged to the 18–25 years age group, followed by 58(39.7%) in the 26–33 years age group, and 14(9.6%) in the 34-49 years age group. Most of them 88(60.3%) had secondary education, followed by 46(31.5%) primary and 12(8.2%) higher education. Regarding employment, 40(27.4%) were employed and 106(72.6%) were unemployed. Most of them 105(71.9%) had first time pregnancy (1st gravida), while 31(21.2%) had 2nd gravida, and 10(6.9%) had third or more gravida. Regarding frequency of daily meals, two times eating habit was reported by 15(10.3%), while three times by 120(82.2%) and four times or more by only 11(7.5%) women. Based on the World Health Organization (WHO) criteria, 5(3.4%) had mild anemia, while 123(84.3%) and 18(12.3%) had moderate and severe anaemia respectively. Among the participants, 20(13.7%) and 23(15.75%) had antepartum and postpartum haemorhage respectively, while 21(14.4%) received blood transfusion. Birth spacing was reported by only 12(8.22%) women. Regarding mode of delivery, 122(83.56%) had history of normal vaginal delivery (NVD) and 24(16.44%) had history of Caesarean section. Anaemia was significantly associated with maternal age, education, daily meals, history of antepartum and postpartum haemorrhage, blood transfusion, birth spacing, and mode of delivery. Conclusion: Regular antenatal checkup and iron supplementation are important to monitor and address any signs of anaemia during pregnancy. International Journal of Human and Health Sciences Vol. 09 No. 03 Jul’25 Page: 159-164